1984
DOI: 10.1002/bjs.1800710326
|View full text |Cite
|
Sign up to set email alerts
|

Surgical experience of deeply jaundiced patients with bile duct obstruction

Abstract: One hundred and twenty consecutive deeply jaundiced patients undergoing surgery for bile duct obstruction were analysed. Diagnosis by either ultrasound or percutaneous transhepatic cholangiography was correct in 84 per cent and 86 per cent of patients respectively. Combination of the two procedures resulted in a diagnostic accuracy of 96.5 per cent. Despite pre-operative antibiotics and intravenous fluids, including Mannitol, infective complications and renal failure were common. Gastrointestinal haemorrhage w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
63
0
8

Year Published

1984
1984
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(74 citation statements)
references
References 30 publications
3
63
0
8
Order By: Relevance
“…The consequences of jaundice are complex and involve a variety of physiologic derangements, including immunosuppression as well as hepatic fibrosis. In particular, patients with jaundice have a predisposition to infection and increased morbidity and mortality (1,2). Altered function of a number of immune effector cells has been implicated in the pathophysiology of jaundice.…”
mentioning
confidence: 99%
“…The consequences of jaundice are complex and involve a variety of physiologic derangements, including immunosuppression as well as hepatic fibrosis. In particular, patients with jaundice have a predisposition to infection and increased morbidity and mortality (1,2). Altered function of a number of immune effector cells has been implicated in the pathophysiology of jaundice.…”
mentioning
confidence: 99%
“…1 Whereas in experienced centers, postoperative mortality has been reduced from 20% to 5%, morbidity remains as high as 50%. 2,3 Most complications have a septic etiology and are considered to be related with translocation of endotoxin from the intestinal lumen into the portal and systemic circulation where an inflammatory cascade is triggered.…”
mentioning
confidence: 99%
“…Many previous studies [3][4][5][6][7] have shown that operating on patients with high bilirubin levels is worse with regard to complications but none, including a large meta-analysis, 30 have suggested a threshold below which surgery without drainage in the non-septic patient is universally acceptable. 13,[26][27][28] This cut-off level of 300 µmol/l is similar to that used in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery in jaundiced patients with pancreatobiliary tumours is associated with a higher rate of postoperative complications. [3][4][5][6][7] Complications of jaundice include haemorrhage, impaired wound healing, renal dysfunction and sepsis (cholangitis, abscesses, anastomotic dehiscence). Relief of jaundice by the percutaneous (percutaneous transhepatic biliary drainage, PTBD) or endoscopic (endoscopic retrograde cholangiopancreatogram, ERCP) route may be considered and have been reviewed in current guidelines.…”
mentioning
confidence: 99%